Pesan Kritik Sosial Guzman Sige - Suryana Khairuddin (UNISBA Press, 2024)
Abstract. Stand-up comedy is rapidly growing in popularity in Indonesia, with shows like Stand Up Comedy Indonesia attracting considerable public interest. The appeal of stand-up comedy lies in its humorous approach, which makes complex messages more accessible and relatable. It often reflects societal values and realities, offering a comedic perspective on social issues. One prominent figure in this genre is Guzman Sige, a notable comedian from Bandung, who has significantly influenced the city's stand-up comedy scene. Sige's performances, including those in the Sebelah Mata Stand Up Comedy Show Bandung, frequently incorporate social criticism. This research, titled